THE EFFECTIVENESS OF SOCIALISATION OF INSURANCE AND BANK PRODUCTS AS A STRATEGY IN ACHIEVING CUSTOMER GROWTH TARGETS - Nadif Ulfia Rahmawati; Yulie Wahyuningsih; Abdul Majid; Jennifer Farihatul Bait (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2025)
PURPOSE The growth of retired customers is crucial to preserving the stability and profitability of Bank Mandiri Taspen's operations as a bank that caters to the pensioner segment. Introducing Ketaspenan and bank products to potential retirees is one of Bank Mandiri Taspen KCP Bojonegoro's tactics in achieving its customer growth goal. The primary issue is that potential customers low level of trust can be affected by their lack of comprehension of the relationship between Bank Mandiri Taspen and PT. Taspen (Persero), both as the holding company and as an institutional organization that oversees the funds of pension participants.METHODOLOGY - This study uses qualitative methods and a case study approach to analyze how effectively this socialization strategy builds trust while reaching customer growth goals. As evidenced by the existence of PT. Taspen (Persero) as a resource, the research findings indicate that this socialization has a significant effect on growing the number of retired customers.FINDING - This study suggests that this socializing approach be maintained going forward in order to enhance Bank Mandiri Taspen's reputation and help it meet optimum customer growth goals.